Estimating Genetic Variability for Yield, Yield Contributing and Fibre Quality Traits in Upland Cotton (Gossypium hirsutum L.) - Kadam, K. V.; Chinchane, V. N.; Mitkari, S. B.; Kute, K. G.; Tirkar, A. N.; Begum, Mohammedi; Matra, N. G. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during the kharif season (July-October, 2022) at Cotton Research Station in Nanded to explore the genetic variability in upland cotton (Gossypium hirsutum L.) using 46 elite genotypes and four reference checks, which had been planted in a Randomized Block Design. The study assessed 13 key traits encompassing morphology, fibre quality, and yield. Understanding the association between yield components and fibre characteristics required data on the diversity and scope of variation, genetic progress, and heritability. Notably, traits such as seed cotton yield plant-1, number of bolls plant-1, number of sympodia plant-1, plant height and boll weight exhibited substantial genotypic and phenotypic variation. Phenotypic variances surpassed genotypic variances across nearly all traits, indicating that the observed variation arose from both genotypes and environmental influences. This suggested that these traits had a strong additive genetic component, making them suitable for efficient improvement through selection. Notably, SCS 793, ARBH 83, SCS 1061, and NDLH 2061-1 emerged as superior genotypes for seed cotton yield per plant, while ARBC 1352, GBHV 180, BWR-152-1, G.Cot 22, CNH 1122, and PH 1060 outperformed the control varieties in terms of fibre quality traits. The study’s findings highlighted that the number of bolls plant-1, plant height, boll weight, number of sympodia plant-1, ginning percentage, lint index, and fibre fineness were the most critical traits for the effective selection of superior American cotton genotypes.